Education for Sustainability, Transformational Learning Time and the Individual <–> Collective Dialectic - VanWynsberghe, Rob (Frontiers in Education, 2022)
In the interest of developing sustainability practitioners, this manuscript challenges the conceptualization of transformative learning for Education for Sustainability (EfS) in relation to single courses or programs. Conversely, I will argue that becoming a sustainability practitioner (i.e., someone who takes action in the interest of the sustainability movement) is life-long and life-wide commitment. Time and how and why it matters is addressed. To develop this point, this manuscript details a case study of an education for sustainability graduate program that I designed and currently lead. The purpose is to further theorize transformative learning as it links individual action(s) and collective change(s) in the border-like but permeable spaces that are in-between. It asks the practical question of the ways educators (and practitioners) might expansively and generatively work together in creating a lifetime of classrooms to continuously bridge individual action and collective change.